Education And Innovation in Management of Underweight Toddlers by Provision Banana Smoothies (Smotbanlit) in Kedoya Utara, Jakarta - Azzahroh, Putri; Gustianingsih; Salvianti, Efti; Rachmasari, Bella; Suryanti; Aquarini; Kartika, Maudy Lila (International Journal of Community Services, 2023)
Background: Community service is an activity that aims to help the community in several activities without expecting rewards in any form. Purpose: The purpose of community service is to educate mothers about the importance of paying attention to their child's weight. Method: The way community service works is by collecting data, determining problem priorities, preparing educational materials, demonstrations of making innovations, then conducting direct counseling to groups of mothers who have toddlers at RT 08 Kedoya Village. Evaluation is carried out by discussion or question and answer. Result: Based on the results of the implementation of community service counseling, there were 5 mothers who had toddlers with substandard nutritional status (BGM) and 11 additional participants including lecturers, midwives and cadres. This activity is carried out together with the team. The participants were very active during the activity with a question-and-answer session. The participants were also willing to accept innovation in the form of toddler banana smoothies (SMOTBANLIT). Conclusion: Providing innovation of toddler banana smoothies to improve digestion so that appetite increases so that they can increase the weight of toddlers with substandard nutritional status.